2000
DOI: 10.1046/j.1365-3016.2000.00275.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessing number‐specific error in the recall of onset of last menstrual period

Abstract: The goal of this investigation was to determine whether women who did not report preferred numbers for their last menstrual period (LMP) may be a group of women who are particularly careful in keeping track of their menstrual cycles and therefore have more accurate LMP dating--based on a comparison with ultrasound examinations. We also sought to estimate the frequency with which preferred numbers are reported in different sources of data and for different subgroups of women. First, we examined the 1987 Califor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
1
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 10 publications
1
41
1
2
Order By: Relevance
“…This includes high level of injectable contraception use, 30 long-term use of which affects return to menses and fertility, limiting LMP reliability. 31 Additionally younger, primigravid women and women with lower educational levels are more likely to misreport LMP. 12,28 Since HIV-uninfected women were more likely to be younger and primigravid it is possible they misreported their LMP more than HIV-infected women, which could explain why the expected association by HIV status was not observed with LMP-GA.…”
Section: Discussionmentioning
confidence: 99%
“…This includes high level of injectable contraception use, 30 long-term use of which affects return to menses and fertility, limiting LMP reliability. 31 Additionally younger, primigravid women and women with lower educational levels are more likely to misreport LMP. 12,28 Since HIV-uninfected women were more likely to be younger and primigravid it is possible they misreported their LMP more than HIV-infected women, which could explain why the expected association by HIV status was not observed with LMP-GA.…”
Section: Discussionmentioning
confidence: 99%
“…A review of reported last menstrual periods collected in California in the 1980s suggested that the numbers 1, 5, 10, 15, 20, 25, and 28 were the most “preferred” recorded times, each occurring more frequently than would otherwise be expected due to chance. Furthermore, when compared with ultrasound estimates of gestational ages, last menstrual periods recorded as a nonpreferred value lead to more accurate gestational age estimates than those last menstrual periods estimated using “preferred” times [16]. Similar to our trend of increasing clustering across time, the proportion of birth weights with zero recorded for the end digit increased as the birth weight itself increased [17].…”
Section: Discussionmentioning
confidence: 56%
“…The proper entry of many numbers and recall biases from the women 9,10 , in a setting of many unplanned pregnancies certainly aid to that. This pattern was seen in both types of birthcare payment (public and private); the latest composed of women with higher socioeconomic level.…”
Section: Discussionmentioning
confidence: 99%
“…LMP-based gestational age is fallible in many cases, such as individual variation of the duration of the menstrual cycle, implantation bleeding, and, particularly, recall biases 9,10 . In Brazil, a high proportion of the population has low schooling -a feature associated to worse quality of information about LMP 5,6 .…”
Section: Introductionmentioning
confidence: 99%